On the Forecastability of Agricultural Output - Kyriazi, Foteini; Xylangouras, Efthymios; Papadogonas, Theodoros (Review of Economic Analysis, 2024)
The disruption of supply chain due to Covid-19 and the war in Ukraine, render the prediction of agricultural output a determinant factor of economic life. We consider the predictability of agricultural output based on a set of explanatory variables, that include agricultural input, prices and consumer demand among others, for Greece and explore the usefulness of these variables compared to standard, univariate, forecasting methods. We evaluate the impact of using combined information in the form of principal components, and the use of averaging for producing accurate forecasts. Our results indicate that agricultural output is predictable and, moreover, we identify the factors that, for the case of Greece, lead to such predictability. Our outcomes can be used in a variety of ways, the least of which can be scenario analysis that might be very useful in real-world policy making.